Da’wah Management Strategy on Social Media to Attract the Millennial Generation - Mahmudah, Siti; Martinez, Isabel; Fernandez, Carlos (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
The increasing reliance on social media has significantly changed how information is shared, including in the realm of Islamic preaching or da’wah. The millennial generation, who are digital natives, represents a key demographic for engaging in da’wah via social media platforms. This study explores the da’wah management strategies used by Islamic organizations and lecturers to attract and engage the millennial generation on social media. Using a qualitative research design, this study analyzes the strategies employed by Islamic organizations to effectively communicate religious messages through social media platforms such as Instagram, YouTube, and Twitter. The findings reveal that interactive content, visual storytelling, and the use of authenticity in messaging are the most effective strategies for engaging millennials. Content that resonates with the values, experiences, and interests of millennials significantly enhances their engagement with da’wah content. The study concludes that social media is a powerful tool for modern da’wah, especially for attracting and influencing the millennial generation. However, the research also highlights challenges such as the need for culturally relevant content and the ethical considerations of using digital platforms for religious outreach. The findings suggest that Islamic leaders should focus on strategic content creation that aligns with the values of younger audiences while maintaining authenticity in their message.